Abstract Algebra Showing that an isomorphism goes both ways.

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Abstract Algebra Showing that an isomorphism goes both ways.

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

Recall that if \(\large\rm f:A\to B\) is a one-to-one function mapping A onto B, then \(\large\rm f^{-1}(b)\) is the unique \(\large\rm a\in A\) such that \(\large\rm f(a)=b\). Prove that if \(\large\rm \phi:S\to S'\) is an isomorphism of \(\large\rm \left\) with \(\large\rm \left\), then \(\large\rm \phi^{-1}\) is an isomorphism of \(\large\rm \left\) with \(\large\rm \left\).
Teacher actually did this one in class... I'm just having trouble with the notation I think.. hmm

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

His notes for showing one-to-one: \(\large\rm \phi^{-1}\) is one-to-one as \(\large\rm \phi^{-1}(a)=\phi^{-1}(b)\) implies that \[\large\rm a=\phi(\phi^{-1}(a))=\phi(\phi^{-1}(b))=b\] I'm just not seeing how that makes use of the original relationship being isomorphic. hmm
showing isomorphic means to show it's homorphism (bijective)
So since \(\large\rm \phi\) is a one-to-one mapping, I'm able to immediately say that \(\large\rm \phi^{-1}\) must also be one-to-one? Is that where I'm starting from? :o
yes exactly :)
hmm with some twist xD
What he wrote for onto: \(\large\rm \phi^{-1}\) is onto as \(\large\rm \phi^{-1}(\phi(x))=x\) for all \(\large\rm x\in S\). Again, I just don't understand how this makes use of phi mapping S onto S' or whatever. I think I can understand the isomorphic property that I have to show after that. I'm just getting confused on these bijective properties.
the twist only a need to make sure phi^-1 fits the origin domain :3
f: A-->B mapping unique 1-1 also onto thus its isomorphic on (s,*) (we call this line phi) u need to show f^-1: B-->A isomorphic on (s',*') means prove that phi^-1 isomorphic by showing f^-1 is 1-1 and onto from B to A notations are clear now @zepdrix ?
Since \(\phi\) is an isomorphism, it is also a homomorphism, so we have \(\phi(xy) = \phi(x)\phi(y)\) for \(x,y\in S\) let \(x = \phi^{-1}(a)\) and \(y = \phi^{-1}(b)\), plug them above : \(\phi( \phi^{-1}(a) \phi^{-1}(b)) = \phi(\phi^{-1}(a))\phi (\phi^{-1}(a))\) \( \implies \phi^{-1}(a) \phi^{-1}(b) = ab\) \( \implies \phi^{-1}(\phi^{-1}(a) \phi^{-1}(b)) = \phi^{-1}(ab)\) that proves the homomorhism part for inverses
Yah, that definitely helps with that portion of it :) Buhaha, you keep editing XD making little corrections
@zepdrix I think what you are missing here is a common thing when talking about inverse relations, that is, we need to prove it is a function. To prove that \(\phi^{-1} :S'\rightarrow S\) is a function you must show that it is 1) Well defined i.e. \(a=b\implies f(a) = f(b)\) and 2) defined everywhere i.e. \(\forall \ x\in S' \ \exists \ y\in S \ \text{ s.t. } f(x) = y\) Now the fact that \(\phi\) is onto, gives that \(\phi^{-1}\) is defined everywhere and the fact that \(\phi\) is one-to-one gives that \(\phi^{-1}\) is well defined.
@zepdrix I think what you are missing here is a common thing when talking about inverse relations, that is, we need to prove it is a function. To prove that \(\phi^{-1} :S'\rightarrow S\) is a function you must show that it is 1) Well defined i.e. (a=b\implies \phi^{-1}(a) = \phi^{-1}(b)\) and 2) defined everywhere i.e. \(\forall \ x\in S' \ \exists \ y\in S \ \text{ s.t. } \phi^{-1}(x) = y\) Now the fact that \(\phi\) is onto, gives that \(\phi^{-1}\) is defined everywhere and the fact that \(\phi\) is one-to-one gives that \(\phi^{-1}\) is well defined.
fixed a few typos...
woops lil boo boo on part 1 :3 lol
bah, now I dont have in my clip board and I am to lazy lol
haha
if you did not use the fact that the original function was well defined to show that the inverse is one to one and if you did not use the fact that the original function was defined everywhere to show that the inverse is onto Then it is wrong. again, I am to lazy to read :)
For the isomorphism part you want to start with two arbitrary elements in \(S'\), say \(a,b\in S'\) and we want to show \(\phi^{-1}(ab)=\phi^{-1}(a)\phi^{-1}(b)\). Now \(\exists x,y\in S\) s.t. \(\phi(x) = a, \phi(y)=b\) So we have \(\phi^{-1}(ab)=\phi^{-1}(\phi(x)\phi(y))=\phi^{-1}(\phi(xy))=xy=\phi^{-1}(\phi(x))\phi^{-1}(\phi(y))=\\\phi^{-1}(a)\phi^{-1}(b)\)
@zzr0ck3r If you get bored, maybe you can read this and see if my wording and steps make sense :) I doubt you'd get THAT bored though lol. --------------------------------------------------------- Since \(\phi:S\to S'\) is an isomorphism of \(\) to \(\), this implies that \(\phi\) is a bijective function. Since \(\phi\) is one-to-one, \(\phi^{-1}\) is well defined. Meaning, that if \(\phi^{-1}(a)=\phi^{-1}(b)\) then \(a=b\) for all \(a,b\in S'\). Since \(\phi\) is onto, \(\phi^{-1}\) is everywhere defined. Meaning, that for all \(x\in S\) there exists a unique element \(y\in S'\) such that \(\phi^{-1}(x)=y\). For \(a,b\in S'\), let \(a=\phi(x)\) and \(b=\phi(y)\). Then \[\phi^{-1}(a*'b)\\=\phi^{-1}(\phi(x)*'\phi(y))\\=\phi^{-1}(\phi(x*y))\\=x*y\\=\phi^{-1}(a)*\phi^{-1}(b)\]--------------------------------------------------------- I used the word "since" a lot, it doesn't read very nicely. Just trying to see if the steps are logical and sufficient.
`I guess I should have inserted`: Therefore \(\phi^{-1}\) is one-to-one `and` Therefore \(\phi^{-1}\) is onto \(S\) `somewhere into there :\` `woops`
you need to prove those two things
o :c hah
\(f:S\rightarrow S'\) is an isomorphism. We want to show \(f^{-1}:S'\rightarrow S\) is a bijective homomorphism. 1) Since \(f\) is onto it follows that \(f^{-1}\) is defined everywhere and since \(f\) is one-to-one it follows that \(f^{-1}\) is well defined. So \(f^{-1}\) is a function. 2) Let \(s\in S\), then \(f(s)\in S'\) that is \(f(s) = s'\) for some \(s'\in S'\) (since \(f\) is defined everywhere). Now \(f(s) = s'\implies f^{-1}(f(s))=f^{-1}(s)\implies s=f^{-1}(s)\). So \[\forall y\in S \ \exists \ x \in S' \text{ s.t. } f^{-1}(x)=y\] that is \(f^{-1}\) is surjective. 3) Suppose \(f^{-1}(a)= f^{-1}(b)\) then, since \(f\) is well defined, \(f(f^{-1}(a))=f^{-1}(f(b))\implies a=b\), showing \(f^{-1}\) is injective. 1), 2), and 3) show that \(f^{-1}\) is a bijection. 4) Suppose \(a,b\in S'\). Then, since \(f\) is onto, \(\exists \ x,y \in S\) such that \(\phi(x) = a, \phi(y)=b\). So \[\phi^{-1}(ab)=\phi^{-1}(\phi(x)\phi(y))=\phi^{-1}(\phi(xy))=xy\\=\phi^{-1}(\phi(x))\phi^{-1}(\phi(y))=\phi^{-1}(a)\phi^{-1}(b).\]
Thanks for the help broski! I should get to sleep while I still can >.<
fo sure. no I love this stuff. :)
gn and may you dream of symmetries of the square

Not the answer you are looking for?

Search for more explanations.

Ask your own question